Competitiveness of avocado (Persea americana Mill) in Mexican tropical rain forest region - Martínez-Castañeda, Francisco Ernesto; García-Matias, Francisco; Velázquez-Torres, Ana Luisa (REVISTA TERRA LATINOAMERICANA, 2022)
The avocado is considered as a prof itable production system and job generator. This fruit is part of the policy of productive reconversion of the State of Mexico. The objective was to evaluate the prof itability and competitiveness at private prices of small-scale in the Tropical Forest Region of the Mexico. the policy analysis matrix was used in its f irst line. The system were agruped into distances and ages. The highest prof itability was $ 23 726 mexican pesos in young systems with distance of 6 meters and the worst performance was $ -24 438 mexican pesos in system of 8 meters distance and from 7 to 9 years of age. The system between 4 and 6 years of age are prof itable and competitive favors the expansion of the cultivar. The plantations older than 10 years of age recorder negative indicators. The yield was evaluated with a split-plot design. No statistical dif ference in yield between the plantations.